PERFORMANCE OF THE DEPARTMENT OF PUBLIC WORKS AND SPATIAL SOUTH BOLAANG MONGGONDOW REGENCY IN HANDLING ROAD AND BRIDGE INFRASTRUCTURE - Siti Fatima Suja; Ismet Susila; Rusli Isa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study conducts an in-depth analysis of the performance of the Department of Public Works and the South Bolaang Mongondow District regarding the management of road and bridge infrastructure, viewed from a normative legal perspective. It evaluates the alignment of these agencies' duties with the mandates of Law Number 2 of 2022 and other technical regulations. Utilizing normative legal research methods, including statutory and conceptual approaches, the study analyzes a range of secondary data comprising both primary and secondary legal materials. The findings indicate that the performance of these services encounters significant legal challenges, particularly concerning the ambiguous legal status of district roads, which complicates budget allocation, alongside inflexible procurement procedures that impede timely responses to infrastructure damage. Furthermore, a disparity exists between physical development and the legal protection of infrastructure due to inadequate local regulations regulating vehicle loads. The study underscores the necessity to bolster local regulations and enhance the technical-juridical capabilities of relevant authorities to ensure that infrastructure development is not only physically secure but also legally accountable, thus contributing to the sustainability of regional accessibility in South Bolaang Mongondow Regency.